2012
DOI: 10.3109/02688697.2012.654835
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of decompressive hemicraniectomy following malignant middle cerebral artery infarctions: a systematic review

Abstract: Decompressive hemicraniectomy has been used increasingly in recent years to treat malignant middle cerebral artery territory infarction. This review examines functional outcome data, with the novel analysis of outcomes according to temporal periods post-surgery. Case series data were pooled to determine significant correlates of outcome. Severe disability was frequently the outcome among survivors within one month post-surgery. Time and rehabilitation were later reflected, with fewer deaths and the emergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Among the patients undergoing DHC in this study, the median NIHSS score on admission was 18 (IQR [14][15][16][17][18][19][20][21][22], the condition exhibited a right-side predominance (73.0%) and the presence of ipsilateral ICA occlusion was detected in 57.2% of patients, although these were not found to be independent factors affecting the 30-day mortality. Interestingly, the occurrence of atrial fibrillation (60.0%) was found to be inversely correlated with mortality, although this finding did not reach statistical significance in the multivariate analysis.…”
Section: Characteristics Of Patients Undergoing Decompressive Hemicramentioning
confidence: 91%
See 2 more Smart Citations
“…Among the patients undergoing DHC in this study, the median NIHSS score on admission was 18 (IQR [14][15][16][17][18][19][20][21][22], the condition exhibited a right-side predominance (73.0%) and the presence of ipsilateral ICA occlusion was detected in 57.2% of patients, although these were not found to be independent factors affecting the 30-day mortality. Interestingly, the occurrence of atrial fibrillation (60.0%) was found to be inversely correlated with mortality, although this finding did not reach statistical significance in the multivariate analysis.…”
Section: Characteristics Of Patients Undergoing Decompressive Hemicramentioning
confidence: 91%
“…Published reports suggest that a poor outcome may be attributable to the presence of herniation, a low preoperative level of consciousness and the involvement of multiple vascular territories in ischemic stroke patients (6,10,15,20). In a meta-analysis of three RCTs, DHC performed within 48 hours of ictus reduced the mortality rate from 71% to 22% and doubled the probability of a favorable functional outcome (mRS ≤3) at one year after surgery (22).…”
Section: Characteristics Of Patients Undergoing Decompressive Hemicramentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 For treatment, decompressive hemicraniectomy surgery may be employed to normalize intracranial pressure and increase survival rate but it provides limited improvement in infarct volume and functional outcomes. 7 Opportunities to identify new directions that may enable treatment of acute stroke, especially in severe cases in which reperfusion has not occurred, must therefore be explored as a matter of urgency.…”
Section: Introductionmentioning
confidence: 99%
“…In this series, 74% of patients had very good outcomes (modified Rankin Scale [mRS] score, 0 or 1). 135 have studied patients with supratentorial infarctions treated with decompressive craniectomy, usually within 48 hours of stroke onset. Three prospective trials showed reduced mortality with hemicraniectomy compared with medical management (22% versus 71% mortality, pooled analysis) in patients <60 years of age, but no individual study showed an improvement in the percentage of survivors with good outcomes (mRS score, 0-3), although this improvement (43% versus 21%) was noted in a pooled analysis.…”
Section: Neurosurgical Options In a Deteriorated Patientmentioning
confidence: 99%